Efficiency of an air circulation decontamination device for micro-organisms using ultraviolet radiation. (September 2021) - Corrêa, T.Q.; Blanco, K.C.; Vollet-Filho, J.D.; Morais, V.S.; Trevelin, W.R.; Pratavieira, S.; Bagnato, V.S.
Summary: Background: The concern with environmental security to avoid contamination of individuals was intensified with the crisis established by SARS-CoV-2. The COVID-19 pandemic has shown the necessity to create systems and devices capable of clearing the air in an environment of micro-organisms more efficiently. The development of systems that allow the removal of micro-droplets mainly originating from breathing or talking from the air was the motivation of this study. Aim: This article describes a portable and easy-to-operate system that helps to eliminate the droplets or aerosols present in the environment by circulating air through an ultraviolet-C (UV–C) reactor. Methods: An air circulation device was developed, and a proof-of-principle study was performed using the device against bacteria in simulated and natural environments. The microbiological analysis was carried out by the simple sedimentation technique. In order to compare the experimental results and the expected results for other micro-organisms, the reduction rate values for bacteria and viruses were calculated and compared with the experimental results based on technical parameters (clean air delivery rate (CADR) and air changes per hour (ACH)). Findings: Results showed that the micro-organisms were eliminated with high efficiency by the air circulation decontamination device, with reductions of 99.9% in the proof-of-principle study, and 84–97% in the hospital environments study, contributing to reducing contamination of individuals in environments considered to present risk. Conclusion: This study resulted in a low-cost and relatively simple device, which was shown to be effective and safe, and could be replicated, especially in low-income countries, respecting the standards for air disinfection using UV-C technologies.